The Walt Disney Company : Disney's California Adventure - Arellano, Freddie; Felder, Mark; Watt, Michael; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Disney's California Adventure was part of an effort to increase traffic to the Disneyland Resort in Anaheim, and entice visitors to extend their vacations. With a goal of at least seven million annual visitors, the park underperformed and was widely criticized. California Adventure threatened to erode Disney's brand equity.
Originally published in Arellano, F., Felder, M., Watt, M., & ORourke, J. S. (2011). The Walt Disney Company: Disneys California adventure. 11-06. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Walt Disney Company; Strategic planning; Amusement parks -- California; Branding (Marketing); Disneyland (Calif.)